Effects of different shade treatments on Melaleuca seedling growth and physiological properties - Qiong Li; Le Zhang; Jienan He; Jian’an Li; Hui Zhang; Yanming Li; Yiyang Gu; Hang Luo; Mengqi Lu; Kaizheng Lu; Li Xiong (BMC Plant Biology)
Abstract In light of the detrimental effects of global warming, exacerbated by the intense sunlight and high temperatures prevalent during summer in southern China, on the growth of Melaleuca alternifolia (M. alternifolia) seedlings, this study sets out to examine the impact of various shading treatments on the growth and physiological attributes of M. alternifolia seedlings, with the aim of determining the optimum shading level. The seedling phase is of paramount importance in the growth cycle and regeneration process of M. alternifolia, as both excessive and insufficient light exposure can negatively influence seedling development. Four shading regimes (CK: no shading; C1: 35–45% shading; C2: 45–50% shading; C3: 60–70% shading) were imposed on M. alternifolia seedlings, following which observations were conducted after a 35-day period. The results reveal that the different shading treatments had a significant effect on the growth and physiological indicators of the seedlings, with the moderate shading treatment (C2) proving to be the most advantageous for seedling growth. Under the C2 treatment, an increase in chlorophyll content was observed in the leaves of the seedlings, accompanied by a decrease in malondialdehyde (MDA) content. Concurrently, there was a reduction in the activities of antioxidant enzymes, namely superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT). Furthermore, the levels of abscisic acid (ABA) and gibberellic acid (GA3) declined, while the concentrations of auxin (IAA), salicylic acid (SA), and cytokinin (CTK) ascended. Leaf anatomical analysis disclosed that, in comparison to the control group, the thickness of the lower epidermis and palisade tissue in the leaves of the seedlings subjected to the C2 treatment exhibited a significant reduction. Additionally, an increase in the number of spongy tissue cells was noted, along with a marked increase in total leaf thickness. Consequently, cultivating M. alternifolia seedlings under shading conditions ranging from 45 to 50% is deemed more favorable. The findings of this study offer novel insights into the adaptive responses of M. alternifolia seedlings to varying light intensities and provide theoretical guidance for the cultivation and management of M. alternifolia seedlings in the southern regions of China.